Left ventricular global longitudinal strain in COVID‐19 recovered patients. Issue 10 (23rd September 2021) - Mahajan, Sudhanshu; Kunal, Shekhar; Shah, Bhushan; Garg, Shobhit; Palleda, Girish M.; Bansal, Ankit; Batra, Vishal; Yusuf, Jamal; Mukhopadhyay, Saibal; Kumar, Suresh; Tyagi, Sanjay; Gupta, Anubha; et al.
Abstract: Objectives: Myocardial injury during active coronavirus disease‐2019 (COVID‐19) infection is well described; however, its persistence during recovery is unclear. We assessed left ventricle (LV) global longitudinal strain (GLS) using speckle tracking echocardiography (STE) in COVID‐19 recovered patients and its correlation with various parameters. Methods: A total of 134 subjects within 30–45 days post recovery from COVID‐19 infection and normal LV ejection fraction were enrolled. Routine blood investigations, inflammatory markers (on admission) and comprehensive echocardiography including STE were done for all. Results: Of the 134 subjects, 121 (90.3%) were symptomatic during COVID‐19 illness and were categorized as mild: 61 (45.5%), moderate: 50 (37.3%) and severe: 10 (7.5%) COVID‐19 illness. Asymptomatic COVID‐19 infection was reported in 13 (9.7%) patients. Subclinical LV and right ventricle (RV) dysfunction were seen in 40 (29.9%) and 14 (10.5%) patients, respectively. Impaired LVGLS was reported in 1 (7.7%), 8 (13.1%), 22 (44%) and 9 (90%) subjects with asymptomatic, mild, moderate and severe disease, respectively. LVGLS was significantly lower in patients recovered from severe illness(mild: ‐21 ± 3.4%; moderate: ‐18.1 ± 6.9%; severe: ‐15.5 ± 3.1%; p  < 0.0001). Subjects with reduced LVGLS had significantly higher interleukin‐6 ( p  < 0.0001), C‐reactive protein ( p  = 0.001), lactate dehydrogenase ( p  = 0.009), serum ferritin ( p  = 0.03), and troponin ( p  = 0.01) levels during index admission. Conclusions: Subclinical LV dysfunction was seen in nearly a third of recovered COVID‐19 patients while 10.5% had RV dysfunction. Our study suggests a need for closer follow‐up among COVID‐19 recovered subjects to elucidate long‐term cardiovascular outcomes.